2v^2-4v+52=

Simple and best practice solution for 2v^2-4v+52= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2v^2-4v+52= equation:


Simplifying
2v2 + -4v + 52 = 0

Reorder the terms:
52 + -4v + 2v2 = 0

Solving
52 + -4v + 2v2 = 0

Solving for variable 'v'.

Factor out the Greatest Common Factor (GCF), '2'.
2(26 + -2v + v2) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(26 + -2v + v2)' equal to zero and attempt to solve: Simplifying 26 + -2v + v2 = 0 Solving 26 + -2v + v2 = 0 Begin completing the square. Move the constant term to the right: Add '-26' to each side of the equation. 26 + -2v + -26 + v2 = 0 + -26 Reorder the terms: 26 + -26 + -2v + v2 = 0 + -26 Combine like terms: 26 + -26 = 0 0 + -2v + v2 = 0 + -26 -2v + v2 = 0 + -26 Combine like terms: 0 + -26 = -26 -2v + v2 = -26 The v term is -2v. Take half its coefficient (-1). Square it (1) and add it to both sides. Add '1' to each side of the equation. -2v + 1 + v2 = -26 + 1 Reorder the terms: 1 + -2v + v2 = -26 + 1 Combine like terms: -26 + 1 = -25 1 + -2v + v2 = -25 Factor a perfect square on the left side: (v + -1)(v + -1) = -25 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

You can always share this solution

See similar equations:

| v^2-4v+16= | | v^2-36= | | 24uxy^5-22u^5y^5= | | 4u^6+6u^5-10u^4= | | 10x^2+12x+18=0 | | 25p^2=4 | | 5x^2=13x+6 | | x^2+10x+25=0 | | X^2+4x+4=0 | | x^2+6x+9=0 | | -4x=2x^2-6 | | -x=2x^2-6 | | -2x=3x^2-1 | | -9x=2x^2-5 | | x^2-5x-6=0 | | x^2-x-12=0 | | 3x^2+5x-13=11-9x | | 5x^3-5x=0 | | 16x^2+2x-3=0 | | 4x^2-25=0 | | x^2-19x=0 | | x^2-x+18=0 | | 13x^2-11x=0 | | 7x^2+4x-15=49-44x | | 3x^3+9x^2+6x=0 | | x^2-3x-18=0 | | x^2-63x+60=0 | | 2x(4x-7)+3=(2x-7)(3x+4)+2x^2 | | 8x^3+10xy+6x^2y^5=0 | | 2X(X^2-4X+7)= | | 2x^2-5x-5=0 | | 2x^2-38x=7x^2-3x-24 |

Equations solver categories